Reputation: 297
Examples:
addElement (1, 1) [(1, 1)] = [(1,2)]
addElement (2, 2) [(1,1),(2, 2)] = [(1,1),(2, 4)]
My code:
addElement :: (Integer, Integer) -> [(Integer, Integer)] -> [(Integer, Integer)]
addElement (a,b) ((x,y):xs)
| a==x = ((x,y+b):xs)
|otherwise = addElement ((a+1), b) xs
I couldn't make it work for the rest of the list.
Upvotes: 0
Views: 317
Reputation: 36451
One might also use a list comprehension to accomplish this:
addElem :: (Eq a, Num b) => (a, b) -> [(a, b)] -> [(a, b)]
addElem (x1, x2) lst = [if x1 == y1 then (y1, x2 + y2) else y | y@(y1, y2) <- lst]
Upvotes: 0
Reputation: 476547
You need to recurse on the function, and for the otherwise
case yield the (x,y)
2-tuple. Furthermore you should implement the case with an empty list:
addElement :: (Eq a, Num b) => (a, b) -> [(a, b)] -> [(a, b)]
addElement _ [] = []
addElement kv@(k1, v1) (kv2@(k2, v2):xs)
| k1 == k2 = ((k2, v1+v2) : addElement kv xs
| otherwise = kv2 : addElement kv xs
You can work with map
to only implement logic that works on a single element, so:
addElement :: (Eq a, Num b) => (a, b) -> [(a, b)] -> [(a, b)]
addElement (k, v) = map f
where f kv2@(k2, v2)
| k == k2 = (k2, v+v2)
| otherwise = kv2
Upvotes: 2